Cingulo-hippocampal effective connectivity positively correlates with drug-cue attentional bias in opioid use disorder. (30th December 2019) - Ma, Liangsuo; Steinberg, Joel L.; Bjork, James M.; Taylor, Brian A.; Arias, Albert J.; Terplan, Mishka; Anastasio, Noelle C.; Zuniga, Edward A.; Lennon, Michael; Cunningham, Kathryn A.; Moeller, F. Gerard
Highlights: This study investigated drug-related attentional bias in opioid use disorder. Dynamic causal modeling was used to assess underlying neural circuits. Opioid cues caused increase in anterior cingulate cortex (ACC) to hippocampus effective connectivity. Greater increase of this connectivity was associated with greater attentional bias. The findings were consistent across opioid use disorder and cocaine use disorder. Abstract: Individuals with opioid use disorder (OUD) often relapse when exposed to opioid-related cues. Previous functional magnetic resonance imaging (fMRI) studies have identified neuronal corticolimbic changes related to drug cue reactivity in OUD. However, the corresponding manner in which brain regions interact is still unclear. Effective (directional) connectivity was analyzed using dynamic causal modeling of fMRI data acquired from 27 OUD participants (13 with OUD and 14 with OUD and cocaine use disorder [OUD+CUD]), while performing an opioid-word Stroop task. Participants were shown opioid and neutral words presented in different colors and were instructed to indicate word color but ignore word meaning. The effects of opioid words relative to neutral words on effective connectivity and on behavioral reaction time were defined as modulatory change and attentional bias, respectively. For all the 27 participants, left anterior cingulate cortex (ACC) to right hippocampus effective connectivity exhibited the largest modulatory change, which was positively correlated with attentional bias. The findings for the ACC to hippocampus EC were consistent across OUD and CUD found in a previous study.